Leisure time activities of Iranian patients with multiple sclerosis: a qualitative study - Seyed Mohammad Sadegh Hosseini; Ali Asgari; Mehdi Rassafiani; Farzaneh Yazdani; Mehrdokht Mazdeh (Tabriz University of Medical Sciences, 2016)
Background: Leisure time is one of the most important aspects of life, especially for people with chronic diseases. The concept and types of leisure have frequently been evaluated in different socio-cultural populations. The aim of this study was to identify the nature of leisure activities among a sample of Iranian patients with multiple sclerosis (MS) and classify the identified types of activities in the context of Iranian culture. Methods: In this qualitative study, semi-structured interview was applied to gather data from 34 MS patients that were selected through purposive sampling. The interviews were continued up to the point of saturation. Content analysis was used to explore experiences of the interviewees regarding their leisure activities. Results: Six categories of leisure activities were extracted for the studied patients with MS i.e.physical, social, individual, art/cultural, educational and spiritual/religious. Conclusion: The results represented the range and heterogeneity of leisure activities amongst the MS patients. Considering participation in spiritual/religious and social activities as leisure time undertaking might reflect cultural diversity in the perception and use of time for recreation. For mental health promotion purposes, paying special attention to the types of activities that people of different socio-cultural background choose for their refreshment could help health care providers in giving tailored advice for patients with MS and other chronic debilitating disease.